Aging population, pension funds and financial markets. Regional perspectives and global challenges for Central, Eastern, and Southern Europe (Washington, DC, 2009)
"Population aging is a worldwide phenomenon, but it is particularly advanced in highly developed northern countries. The retirement of the baby-boom generation in these rich countries will impose additional, albeit temporary, pressure on their pension systems. To cope with this pressure, reforms have been introduced that have lessened the generosity of publicly provided pension benefits. By design and by implication, this change increases the importance of mandatory and voluntary funded retirement schemes in smoothing consumption across the life cycle. The first three chapters of this book investigate questions germane to pension systems in the Central, Eastern, and Southern Europe (CESE) economies: the extent to which pension systems were prepared to deal with multi pillar pension reform, how to foster the development of financial systems so that they can better support funded systems, and how ready the systems are for the approaching payout of benefits as the first participants in the funded pillar approach retirement age. The remaining three chapters investigate broader questions facing pension systems in both developed and emerging countries: the capacity of the financial markets to deliver sufficiently high net rates of return, the benefits and disadvantages of investment in emerging markets, and the effect of aging on the rates of return afforded by funded and unfunded schemes."